Keterkaitan antara electronic word of mouth, citra destinasi dan minat berkunjung ke gunung dempo - Heri Setiawan; Sari Lestari Zainal Ridho; Devita Juni Yanti (Faculty of Economics and Business Mulawarman University, 2019)
This study aims to investigate direct effect of electronic word of mouth on destination image and travel intention, direct effect destination image on travel intention, and indirect effect of electronic word of mouth on travel intention through destination image. Data were collected through by online questionnaires with a total sample of 155 respondents. The sampling technique used purposive sampling, with criteria are people who have never been visit to Dempo Mountain area, age criteria among 18-35 years old, living in Palembang City, and who had seen content regarding tourist attraction of Dempo Mountain area in social media. Data analysis used descriptive analysis and path analysis with SPSS program. The results of this study showed that: electronic word of mouth has a positive and significant direct effect on destination image and has a positive and significant direct effect on travel intention, destination image has a positive and significant direct effect on travel intention, and electronic word of mouth has an indirect effect on travel intention through destination image.